ANALISIS YURIDIS CABANG PEMERINTAHAN KEEMPAT DALAM STRUKTUR KETATANEGARAAN DI INDONESIA - Arbani, Tri Suhendra (Wacana Hukum, 2018)
AbstractThe development of the modern state system is also followed by the establishment of new institutions as a support of the institutions that have been there before. The most significant event in the development and establishment of institutions is the new power branch, which is called by the experts in constitutional as an independent state commission. Independent state commission institution which, if seen from the character and the authority, the agency in some literature in American constitutional law is referred to as the fourth branch of power (The Fourth Branch of Government). Some things that make this institution called the fourth branch of government (The Fourth Branch of Government) is the fact that the agency, or commission or the state body run more than one function of government as well. The existence of a fourth branch of government (The Fourth Branch of Government) with the characteristics of state institutions whose authorities are quasi, combinations, as well as the accumulation of three existing government functions and make this institution to be difficult to identify in thought Trias Politica. The phenomenon of the rise of an institution with a new concept that has influenced the constitutional system in many countries.AbstrakPerkembangan sistem ketatanegaaran modern dikuti pula dengan terbentuknya lembaga-lembaga baru sebagai penunjang dari lembaga yang telah ada sebelumnya. Hal yang paling signifikan dalam perkembangan dan pembentukan institusi domokratis tersebut tidak lain adalah cabang kekuasaan baru yang biasa disebut oleh kalangan ahli tata negara sebagai komisi negara independen.  Lembaga komisi negara independen yang jika dilihat dari sifat dan kewengannya, lembaga tersebut dalam beberapa literatur hukum tata negara di Amerika disebut sebagai cabang kekuasaan keempat (The Fourth Branch of Goverment). Beberapa hal yang membuat lembaga negara ini disebut sebagai cabang pemerintahan keempat (The Fourth Branch of Government) adalah fakta bahwa lembaga, atau komisi atau badan negara tersebut menjalankan lebih dari satu bahkan ketiga fungsi pemerintahan sekaligus. Eksistensi cabang pemerintahan keempat (The Fourth Branch of Government) dengan karakteristik lembaga negara yang kewenangannya yang bersifat kuasi, kombinasi, maupun akumulasi dari tiga fungsi pemerintahan yang ada dan menjadikan lembaga ini untuk sulit diidentifikasi dalam pemikiran Trias Politica. Fenomena munculnya sebuah lembaga dengan konsep baru tersebut telah ikut mempengaruhi sistem ketatanegaraan dibanyak negara.